Partisipasi Masyarakat pada Musyawarah Perencanaan Pembangunan Desa/Kelurahan di Kecamatan Airmadidi Kabupaten Minahasa Utara - Wagiu, Vicky Barthel; Kaunang, Markus .; Londa, Very Y (JURNAL ILMIAH SOCIETY, 2015)
District of Airmadidi is one of North Minahasa District in the construction while the major project where the role of the community is expected to support the development programs that exist, one of which development planning. The purpose of this study was to determine the Community participation in activities musrenbang in villages / wards in District Airmadidi but in reality people's participation is still low recorded in the documents of Villages of the activities that brought the level of the District Musrenbang then District only a small portion can be realized. This is causing apathy and skepticism of some people to engage in Musrenbang. This study used qualitative research methods, by conducting interviews, observation and use of documents that are directly related, with a sample of two villages and two villages in the District Airmadidi. Results of research on the level of community participation in Development Planning Village / wards in District Airmadidi North Minahasa Regency, it can be concluded that there are differences in the participation of rural communities and communities that exist in the village where the people in the village a more pro-active in Musrenbang compared to existing communities in the Village District of Airmadidi that apathy toward musrenbang activities based on the information obtained through interviews in several informants in the village and village. Keywords: Community, Participation, Development Planning